Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00243
|View full text |Cite
|
Sign up to set email alerts
|

Dysgonomonas

Abstract: Dys.go.no.mo'nas. Gr. pref. dys ‐ with notion of hard, bad, unlucky; Gr. n. gonos that which is begotten, reproduction; Gr. fem. n. monas a monad, unit; N.L. fem. n. Dysgonomonas intended to mean a weakly growing monad. Bacteroidetes / Bacteroidia / Bacteroidales / Porphyromonadaceae / Dysgonomonas Coccobacilli to short rods. Nonmotile. Gram‐negative. Facultatively anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…The abundance of Firmicutes and Actinobacteria increased to 20.4 and 1.6%, respectively, while the abundance of Bacteroidetes slightly dropped to 6.9% on day 345. A few members within Firmicutes, Actinobacteria, and Bacteroidetes are known as anaerobic fermenters, which have been reported to be capable of fermenting organic carbons (e.g., monosaccharide) to produce SCFAs. Our analysis showed the enrichment of Propionicimonas , Proteiniphilum , and Dysgonomonas over time, and these microorganisms are known for their putative capability to produce acids, e.g., acetic and propionic acids, as fermentation products. Sporolactobacillus and Propionispora , affiliated with Firmicutes, were enriched with high abundances of 12.1 and 6.1%, respectively, on day 345. Sporolactobacillus and Propionispora have been reported to be capable of fermenting organics (e.g., fructose and glucose) to produce acids. , Similar to Sporolactobacillus and Propionispora , Pelosinus that was enriched with an abundance of 1.8% on day 129 can produce acids from glucose or other sugars …”
Section: Resultsmentioning
confidence: 79%
“…The abundance of Firmicutes and Actinobacteria increased to 20.4 and 1.6%, respectively, while the abundance of Bacteroidetes slightly dropped to 6.9% on day 345. A few members within Firmicutes, Actinobacteria, and Bacteroidetes are known as anaerobic fermenters, which have been reported to be capable of fermenting organic carbons (e.g., monosaccharide) to produce SCFAs. Our analysis showed the enrichment of Propionicimonas , Proteiniphilum , and Dysgonomonas over time, and these microorganisms are known for their putative capability to produce acids, e.g., acetic and propionic acids, as fermentation products. Sporolactobacillus and Propionispora , affiliated with Firmicutes, were enriched with high abundances of 12.1 and 6.1%, respectively, on day 345. Sporolactobacillus and Propionispora have been reported to be capable of fermenting organics (e.g., fructose and glucose) to produce acids. , Similar to Sporolactobacillus and Propionispora , Pelosinus that was enriched with an abundance of 1.8% on day 129 can produce acids from glucose or other sugars …”
Section: Resultsmentioning
confidence: 79%
“…Bootstrap values of ≥50% are indicated at their respective nodes. Reference type strains are indicated with superscript “†.” The backgrounds of the reference strains are colored according to the sugar (sucrose and/or glucose) utilization capacity of those bacteria based on the data from (1) Lee et al ( 2013 ); (2) Staley ( 1984 ); (3) Kuykendall et al ( 2015 ); (4) Dall'Agnol et al ( 2013 ); (5) Baldani et al ( 2015 ); (6) Hungria et al ( 1993 ); (7) Kuykendall ( 2015 ); (8) Sajnaga and Jach ( 2020 ); (9) Ahnia et al ( 2018 ); (10) Reis et al ( 2004 ); (11) Chen et al ( 2006 ); (12) Coenye et al ( 2001 ); (13) Wolterink et al ( 2005 ); (14) Weon et al ( 2008 ); (15) Qiu et al ( 2017 ); (16) Hardoim et al ( 2013 ); (17) Xu et al ( 2020 ); (18) Ueki et al ( 2006 ); (19) Olsen ( 2015 ); (20) Imhoff ( 2015b ); (21) Diaz-Barrera et al ( 2016 ); (22) Bae et al ( 2006 ); (23) Norris et al ( 2015 ); and (24) Patrick and McDowell ( 2015 ). The black-and-white shading in the columns on the right-hand of the NifH-OTU name indicates the mean relative abundance of the NifH-OTUs in each rice genotype ( n = 2 for Nipponbare; n = 3 for agpl1 , Leafstar, and CG14).…”
Section: Resultsmentioning
confidence: 99%
“…Propionspora affiliated with Clostridia, and Dysgonomonas affiliated with Bacteriodia were the dominant genera during start-up phase, accounting for, respectively, 29.1% and 19.4% of the whole community. Members of Clostridia (32.2%) and Bacteriodia (23.5%) were significantly enriched, and it has been reported that many species of Clostridia and Bacteriodia can produce organic acids by fermenting organic carbon. , Propionspora and Dysgonomonas are known for their capacity to produce acids, for example, acetate and propionate, as fermentation products. , It is worth mentioning that Methanomicrobia accounted for 3.1% of the community (SI Figure S1), yet the dominant genus was no longer Candidatus ‘Methanoperedens’. It was replaced by Methanosarcina , which is an anaerobic methanogen that utilizes H 2 /CO 2 or acetate to produce methane .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, heterotrophic bacteria such as Azospira and Dechloromonas were enriched, possibly due to the presence of easily utilized carbon sources such as acetate and propionate in the reactor. In the continuous phase, while the abundance of Clostridia, Betaproteobacteria, and Bacteriodia decreased, diverse microorganisms capable of producing acids were abundant, ,, with Propionispora , Syntrophomonas , Propionicimonas , Dysgonomonas , and Proteiniphilum in combination accounting for 19.6% of the whole community. The relative abundances of Methanomicrobia and Methanobacteria were obviously higher than in the start-up phase (SI Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation